Political Empowerment of Women in India: A Study of Their Participation and Share in Power Structure - Dilip Kumar R.; Duraish Kumar, M.V. (Bihar Journal of Public Administration)
The role of woman in India for the better part of known history have been more domestic, than public. Though it is believed that in some stretch of historical era, women enjoyed equal status with men in India, the near history has full of unequal practices and impartial treatment towards Though currently women match men in all walks of life her presence in political arena had been found wanting. Thus it is imperative to match presence of women in the political arena with that of men. As per the Inter Parliamentary data 24.5% of women are in the National Parliaments across the globe. India, with 14.36% of women representatives in lower house and 10.61% in upper house, ranks 143 out of 190 countries in the presence of women in the national law making body. Also through these years the share of women contestants was only around 10%. Their share in power structure (ministerial berths) has also been discouraging. Only a change in mindset of the political heavyweights and a change in overall attitude of society towards the need for women$1 (Bs political empowerment can truly empower women in political spheres. - Reproduceds
Keywords: Political Empowerment; Political Participation; Power Structure; Reservations; Feminism